2006
DOI: 10.1074/jbc.m605814200
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Analysis of the Shal (Kv4) Voltage-gated Fast Transient K+ Channel in Caenorhabditis elegans

Abstract: . We show that Shal channels also play a role as the predominant transient outward current in Caenorhabditis elegans muscle. Green fluorescent protein promoter experiments also revealed SHL-1 expression in a subset of neurons as well as in C. elegans body wall muscle and in male-specific diagonal muscles. The shl-1 (ok1168) null mutant removed all fast transient outward current from muscle cells. SHL-1 currents strongly resembled Shal currents in other species except that they were active in a more depolarized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 59 publications
1
33
1
Order By: Relevance
“…They not only promote the biogenesis of SHL-1 K ϩ current, but also modulate the current characteristics in muscle cells. Previous studies have demonstrated that the SHL-1 native channels activate in a more hyperpolarized voltage (ϳϪ14 mV shift) than the cloned channels expressed in heterologous systems (Santi et al, 2003;Fawcett et al, 2006;Wu et al, 2010). Our data reveal that the discrepancy could be due to the existence of ceKChIPs.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…They not only promote the biogenesis of SHL-1 K ϩ current, but also modulate the current characteristics in muscle cells. Previous studies have demonstrated that the SHL-1 native channels activate in a more hyperpolarized voltage (ϳϪ14 mV shift) than the cloned channels expressed in heterologous systems (Santi et al, 2003;Fawcett et al, 2006;Wu et al, 2010). Our data reveal that the discrepancy could be due to the existence of ceKChIPs.…”
Section: Discussioncontrasting
confidence: 45%
“…Since then, the components of K ϩ currents in muscle cells have been well documented. Three K ϩ channels, SHK-1, SHL-1, and SLO-2, were reported to constitute the macroscopic outward K ϩ currents in muscle cells (Yuan et al, 2000;Santi et al, 2003;Fawcett et al, 2006;Gao and Zhen, 2011;Liu et al, 2011). Under physiological conditions with low intracellular concentrations of Cl Ϫ (4 -10 mM) and Ca 2ϩ (10 -100 nM), K ϩ currents with typical fast transient outward components were elicited by a series of voltage steps applied from Ϫ80 to ϩ80 mV (in 20 mV increments) from a holding potential of Ϫ80 mV in cultured myocytes of N2 worms (Fig.…”
Section: Shl-1 Forms Functional Complex With Cekchips In Body Wall Mumentioning
confidence: 99%
“…1) in the N terminus of KVS-1 (dubbed K1 in this "Result" section) exhibited homology to the N-inactivating domains in several A-type ␣-and ␤-subunits (7,9,(35)(36)(37)(38). This suggests that inactivation in K1 might proceed through a N-type mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…positive voltage range than their mammalian counterparts. We showed this to be true for the Shaker (Kv1) and Shal (Kv4) channels (Fawcett et al, 2006) and Shaw (Kv3) EGL-36 channels (Johnstone et al, 1997). In fact, an egl-36 mutation that shifted the voltage dependence of activation of Shaw EGL-36 channels to more negative voltages typical of mammalian channels resulted in excessively active Shaw EGL-36 channels producing the egl phenotype.…”
Section: Voltage Range Of Camentioning
confidence: 90%
“…Figure 2 A shows a family of KVS-1 currents expressed in Xenopus oocytes and evoked by depolarizing step pulses to progressively more positive voltages using two-electrode voltage clamp (TEV). In comparison, Figure 2 B shows a family of currents from the C. elegans Shal (Kv4) ortholog (nShal) (Fawcett et al, 2006). These two families of currents resemble each other with regard to their fast activation and rapid inactivation.…”
Section: Kvs-1 Channels Undergo Camentioning
confidence: 99%